2007
DOI: 10.1111/j.1743-7563.2007.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian preservation with gonadotropin‐releasing hormone analog during chemotherapy

Abstract: Objective: After the improved long-term survival in young women with cancer undergoing chemotherapy, the preservation of their future fertility has been the focus of recent interest. We studied whether gonadotropin-releasing hormone (GnRH) analogs could prevent the early onset of ovarian insufficiency post-chemotherapy and protect fertility. Methods: The patients were divided into two groups. Group A consisted of post-menarche patients aged 12-45 years (n = 15), who received chemotherapy but no GnRH analog pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Previously published randomized studies with GnRH-a during HL chemotherapy evaluated the rate of chDOR after non-standardized chemotherapy regimen [16,18]. Our study confirmed significant differences in fertility outcomes among different chemotherapy groups and thus suggested optimum chemotherapy regarding fertility preservation in HL patients.…”
Section: Discussionsupporting
confidence: 78%
“…Previously published randomized studies with GnRH-a during HL chemotherapy evaluated the rate of chDOR after non-standardized chemotherapy regimen [16,18]. Our study confirmed significant differences in fertility outcomes among different chemotherapy groups and thus suggested optimum chemotherapy regarding fertility preservation in HL patients.…”
Section: Discussionsupporting
confidence: 78%
“…1) (11)(12)(13)(14)(15)(16)(17)(18). A total of 321 women were treated with GnRHa during their chemotherapy, while 300 women underwent chemotheray without GnRHa.…”
Section: Resultsmentioning
confidence: 99%
“…Among the trials in our analysis, four (11,14,16,18) were conducted on patients younger than 40 years. Because of the limited data, we could not estimate the precise function of GnRHa in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…A total of six randomized trials in patients with breast cancer [51][52][53][54][55][56] and one in women with ovarian cancer (which was positive) [57] have been published. Conflicting results on the efficacy of this strategy have been reported in these trials; however, several limitations of these studies should be considered [58].…”
Section: Ovarian Suppression With Luteinizing Hormone-releasing Hormomentioning
confidence: 99%